Clinical paratuberculosis (Johne’s disease) and chronic mastitis can be successfully treated with a novel therapy in dairy cows – a case report - Németh, Attiláné; Sensen, Mária (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
Paratuberculosis, a thus far untreatable infectious disease of ruminants has been known for more than a hundred years. While subclinical infections cause severe financial losses, the development of clinical symptoms results in inevitable premature death of the animals. Its causative agent, Mycobacterium avium subspecies paratuberculosis (MAP) is distributed worldwide, however, due to its limited diagnosis at subclinical stage, controling the spread of the disease is difficult. It has a significant impact on milk production, fertility and increased incidence of mastitis. Mastitis is the most costly disease of dairy farms, as it can effect as high as 40% of the herds. In this report we present a new approach to therapy, in wich, without any application of antibiotics or steroids, using exclusively natural herbal remedies, we have been able successfully to cure a five and half year old, naturally-infected dairy cow - manifesting the clinical signs and symptoms of paratuberculosis and chronic mastitis - within six weeks. The MAP negative fecal culture supports the complete cure. To our knowledge the therapy applied by us is the first proven remedy for curing clinical paratuberculosis.
Keywords: Johne’s disease; Mycobacterium avium subspecies paratuberculosis; mastitis; herbal therapy; anti-inflammatory effect